Peran Kepemimpinan Kekewirausahaanan dan Orientasi Kekewirausahaanan yang Dimediasi oleh Keunggulan Kompetitif untuk Meningkatkan Kinerja Bisnis Pada Usaha Mikro dan Kecil di Kota Semarang (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to examine the impact of entrepreneurial leadership and entrepreneurial orientation on business performance, with competitive advantage acting as a mediating variable, among Micro and Small Enterprises (MSEs) in Semarang City. The research employs an explanatory research design with a quantitative approach. Data were collected through questionnaires distributed to 208 MSE actors selected by purposive sampling. Data analysis was conducted using Structural Equation Modeling with the Partial Least Square (SEM-PLS) method via SmartPLS 4 software. The results indicate that entrepreneurial leadership has a positive and significant effect on entrepreneurial orientation; entrepreneurial orientation positively and significantly influences competitive advantage; entrepreneurial leadership also positively and significantly affects competitive advantage; competitive advantage positively and significantly impacts business performance; entrepreneurial orientation has a positive and significant effect on business performance; and entrepreneurial leadership directly exerts a positive and significant influence on business performance. These findings confirm that the synergy between entrepreneurial leadership, entrepreneurial orientation, and competitive advantage is a key factor in enhancing MSE performance amid changing competitive dynamics. The managerial implications derived from this study can serve as strategic guidelines for MSE actors and policymakers in formulating strategies to support MSE development